Pengaruh Perbedaan Waktu Tanam Tetua Padi Hibrida dan Aplikasi Zat Pengatur Tumbuh terhadap Hasil Benih F1 HIPA 8 - WAHYUNI, SRI; RUSTIATI, TITA; WIDYASTUTI, YUNI (Agrotrop : Journal on Agriculture Science, 2015)
The Effects of Planting Time of TheParental Hybrid Rice and Plant Growth RegulatorApplication on Seed Yield of F1 HIPA 8.Research the effect of planting time of parental lines andapplication of plant growth regulators (GA3and glysine) on seed yield of F1 hybrid rice had beenconducted at The Indonesian Centre of Rice Research on 2010. The objective of the study was to findout combination of plating time and application of plant growth regualtors to get high seed yield ofhybrid rice. Seeds of parental lines Hipa 8 were planting in row ratio 2R:8A at Cilandak, Indramayu onthe dry season of 2010. Treatments to improve seed yield of hybrid rice consisted of (a) planting timeof parental lines (CMS and R), and (b) application of plant growth regualators (GA3 CG1 (commercialgrade) 60 ppm, GA3 CG2 94 ppm, Glysine 40 ppm and control (untreated). Plant growth regualatorwere applied at three times i.e. heading time, 5% plant flowering and 20% plant flowering. Variableevaluated consisted of: plant growth, yield component and seed yield. Result of the exeperiment showedthat tiller number per hill and plant height at vegetatif stage were not affected by treatments. TreatmentA1B2 and A2B2 significantly improved panicle exercition, plant height of restorer and also seed yield.Rice plant treated with A1B2 (planting times of restorer were 12, 15, and 18 days after CMS andapllication GA3 CG1 60 ppm) showed the highest seed yield, followed by A2B2 (planting times ofrestorer were 13, 17 and 21 days after CMS and application of GA3 CG1 60 ppm).
Keywords: plant growth regulator; seed yield; hybrid rice